Aktualisasi Sila Pertama Terhadap Karakter Religius Generasi Muda di Era Society 5.0 - Syafii, Imam; Amelia, Rindu; Priliano, Brian; Maulindah, Dela; Jannah, Siti Nur Sofirotul; Bilqisti, Alfath (Jurnal Kependidikan Islam, 2024)
Indonesia's young generation as the nation's successor is required to be able to adjust to the development of digital technology in the Era of Society 5.0. Digitalization has a huge impact on the character of the younger generation, especially the religious character which is currently fading. The actualization of the first precept towards religious character is needed for the younger generation to improve their spirituality. This study aims to understand the relationship of the first precept to the improvement of the religious character of the younger generation in the 5.0 era. The research method used is descriptive analysis with a mixed approach (Mix Method). This research uses data collection techniques in the form of distributing questionnaires to respondents, which are then reviewed using literature review or literature study from related sources. The results of this study indicate that the actualization of the first precept is an important part of creating a religious character of the younger generation, because it has a strong relevance to one's personality. This study seeks to improve the religious character of the younger generation by implementing the noble values contained in the first precept of Pancasila.